Combining SERRS and electrochemistry to characterize sensors based on biomembrane mimetic models formed by phospholipids - Alessio, Priscila [UNESP]; Aoki, Pedro H. B. [UNESP]; De Saja Saez, J. A.; Rodriguez-Mendez, M. L.; Constantino, Carlos J. L. [UNESP] (Royal Soc Chemistry, 2011)
The surface-enhanced resonance Raman scattering (SERRS) technique and an electronic tongue system based on cyclic voltammetry were coupled combining structural information and sensitivity. Layer-by-Layer (LbL) films containing the phospholipids cardiolipin (CLP) and dipalmitoyl phosphatidyl glycerol (DPPG) were deposited onto ITO to obtain functional electrodes forming an array of sensing units. The phospholipids were applied here as biological membrane mimetic systems, taking advantage of their affinity with pharmaceutical drugs. The electronic tongue was used in the detection of methylene blue (MB) at micromolar concentrations. SERRS spectra were also collected directly from the sensing units (in situ SERRS), which was possible due to the adsorption of Ag nanoparticles (AgNPs) within the phospholipid LbL films. This approach also induced an enhancement of the voltammetric signal of the sensing units, especially in the case of CLP. Complementary, the LbL films were morphologically characterized using micro-Raman and scanning electron microscopy-field emission gun (SEM-FEG).